The association of calcaneal spur length and clinical and functional parameters in plantar fasciitis - Kuyucu, Ersin; Koçyi?it, Figen; Erdil, Mehmet Emin (Elsevier, 2015)
Introduction: Plantar fasciitis (PF) is the most common cause of plantar heel pain. Despite many treatment alternatives for heel spur, the association of calcaneal spur size with clinical and functional parameters is inconclusive. The objective of this study to investigate the correlation of calcaneal spur length with clinical findings and functional status documented with Foot Function Index in patients with plantar fasciitis. Methods: We performed power analysis for the sample size estimation. 87 patients with PF were scrutinized to reach the estimated patient number 75. Computer-aided linear measurements were done for spur length from tip to base in milimeters. Perceived pain intensity was evaluated by visual analog scale (VAS). Patients were asked to rate the pain experienced on a 10-cm VAS. Foot function index was applied to the patients to evaluate pain, disability and activity limitation of the patients. Results: Of the 75 participants, 24 were males (32%) and 51 were females (68%). The mean age was 47 +/- 10 years (range 30-65 years). The mean calcaneal spur length was 3.86 +/- 3.36 mm (range between 0 and 12.2). Calcaneal spur length was significantly correlated with age (p = 0.003), BMI (p = 0.029), symptom duration, (p = 0.001) VAS (p = 0.003), and FFI total score (p < 0.001). Discussion: Our study demonstrated that length of the calcaneal spur is significantly correlated with age, BMI, symptom duration, perceived pain, FFI pain and disability subscores, and FFI total scores. Conclusion: The size of the calcaneal spur is an important parameter correlated with pain and functional scores in PF.
WOS: 000360993700006
PubMed ID: 26184993
Keywords: Roentgenography; Heel Spur Syndrome; Body Mass Index; Musculoskeletal Disease